Diagnostic yield of additional conventional transbronchial lung biopsy following radial endobronchial ultrasound lung biopsy for peripheral pulmonary lesions. Issue 6 (27th April 2020) - Park, Sojung; Yoon, Hee‐Young; Han, Yeji; Wang, Kyung Sook; Park, So Young; Ryu, Yon Ju; Lee, Jin Hwa; Chang, Jung Hyun
Abstract: Background: Radial endobronchial ultrasound (R‐EBUS) transbronchial lung biopsy (TBLB) improves the diagnostic yield from peripheral pulmonary lesions (PPLs). However, the small specimens obtained using small forceps through a guide sheath (GS) may impede diagnosis and molecular analysis. Here, we investigated the diagnostic significance of additional conventional TBLB with standard forceps after R‐EBUS‐GS‐guided TBLB. Methods: We retrospectively reviewed data from 55 patients who underwent conventional TBLB after R‐EBUS‐GS‐guided TBLB for PPL diagnosis. Procedures were performed on single PPLs with no visible lesions on bronchoscopy. In cases with inconclusive pathologic confirmation, final diagnoses were made based on pathologic specimens or clinical observations. Results: The median size of the target lesions was 28 mm. The appearances on computed tomography images were solid ( n = 45, 81.8%), part‐solid ( n = 7, 12.7%), and cavitary nodules ( n = 3, 5.5%). A computed tomography bronchus sign was present in 35 (63.6%) cases, and a radial probe was positioned within target lesion in 32 (58.2%) cases. R‐EBUS‐GS‐guided TBLB was diagnostic in 30 (54.5%) patients, and subsequent conventional TBLB yielded additional diagnostic information in 8 (14.5%) patients. Probe positioning within target lesions and the outer margin of PPLs more than 1 cm from pleura were significantly associated with enhanced diagnostic yield from the combined procedures. In conventional TBLB, probe positioning within target lesions (75.0% vs. 11.8%, P = 0.004) and characteristic of nonsolid nodules (83.3% vs. 15.8%, P = 0.006) were significantly associated with additional diagnostic utility. Conclusions: Conventional TBLB following R‐EBUS‐GS‐guided TBLB could be a useful procedure for diagnosing PPLs, especially for nonsolid nodules. Key points: Significant findings of the study: Additional conventional TBLB with standard forceps after R‐EBUS‐GS‐guided TBLB yielded an additional 14.5% diagnostic utility for peripheral pulmonary lesions. For conventional TBLB, probe positioning within target lesions and nonsolid nodules were significantly associated with additional diagnostic utility. What this study adds: Conventional TBLB with standard forceps after R‐EBUS‐GS‐guided TBLB is an effective and economically accessible diagnostic tool for peripheral pulmonary lesions.